Performance of metallic defences submitted to vehicle impact. Issue 3 (3rd May 2016) - Driemeier, L.; Yoneda, A.; Moura, R. T.; Alves, M.
Abstract: The main function of a road guardrail is to redirect an out of control vehicle avoiding a frontal collision or a dangerous veering off the road trajectory. Second, the energy absorption imposed by barrier deformation or any other energy dissipation method is beneficial to the car occupant safety. This study evaluates the performance of a W-Beam guardrail system, in accordance to Brazilian Standards, in respect to the kinetic energy absorption and to the vehicle return angle to the road. This evaluation of the guardrails is performed in a virtual environment using the finite element method. For the correct representation of the model, the material was characterised through experimental tests. Simplifications in the model are taken from the literature and a validated model of a vehicle is provided by the US National Crash Analysis Center.